Design and Field-Scale Demonstration of Pre-Fracturing with a Practical Model for the Size Estimation of Blast-Induced Damaged Zone - Yim, Juhyi; Jung, Jae Hoon; Kang, Han Byul; Shin, Young Jin (Archives of Mining Sciences, 2026)
Pre-fracturing is introduced as an auxiliary method for mechanical excavation, aiming to weaken the hard rock and control the Excavated Damaged Zone (EDZ). Pre-fracturing necessitates re-optimised charge and hole layouts due to its objectives, which differ from conventional single-free-face blasting. This motivates a rigorous estimator of the blast-damage extent surrounding a blast hole. A practical model for estimating the Blast-Induced Damaged Zone (BIDZ) around a blast hole was analytically derived under quasi-static conditions while accounting for dynamic rock strength, in-situ stress, spherical symmetry, and blast-induced changes in hole radius. The validity of the practical model was confirmed via comparisons with dynamic numerical models, empirical relations, and experimental data from previous research. The practical model shows good agreement with empirical relations and reproduces trends observed in dynamic numerical simulations, with discrepancies below 45% across the tested conditions. Based on experimental data, the maximum crack length from a blast hole was approximately 1.3 times the BIDZ estimated by the practical model. A field-scale demonstration of pre-fracturing was conducted on a hard-rock quarry slope. Rock weakening with decreasing hole spacing was verified through surface observations and laboratory tests. The EDZ extent was effectively controlled to 9-10 cm from the contour, which is below the typical extent produced by the conventional excavation method. Based on the pre-splitting cases and the present field demonstration, the optimal hole spacing was proposed as 1.5-3.0 times the BIDZ estimated by the practical model. A blast-pattern design for pre-fracturing is also suggested, considering the optimal hole spacing and maximum crack length estimate based on the practical model.